Measuring service quality: The opinion of Europeans about utilities - Pieralda A. Ferrari; Silvia Salini (Fondazione Eni Enrico Mattei (FEEM), 2008)
This paper provides a comparative analysis of statistical methods to evaluate the consumer perception about the quality of Services of General Interest. The evaluation of the service quality perceived by users is usually based on Customer Satisfaction Survey data and an ex-post evaluation is then performed. Another approach, consisting in evaluating Consumers preferences, supplies an ex-ante information on Service Quality. Here, the ex-post approach is considered, two non-standard techniques - the Rasch Model and the Nonlinear Principal Component Analysis - are presented and the potential of both methods is discussed. These methods are applied on the Eurobarometer Survey data to assess the consumer satisfaction among European countries and in different years.
Keywords: C33; C35; C43; L94; L95; L96; 330; Service Quality; Eurobarometer; Non Linear Principal Component Analysis; Rasch Analysis; Conjoint analysis; Dienstleistungsqualität; Konsumentenverhalten; Kundenzufriedenheit; Messung; Statistische Methode; EU-Staaten